Deterministic observation theory and applications - Gauthier, Jean-Paul (Cambridge University Press, 2001)
This book presents a general theory as well as constructive methodology in order to solve 'observation problems', that is: reconstructing the full information about a dynamical process on the basis of partial observed data. A general methodology to control processes on the basis of the observations is also developed. Illustrative but practical applications in the chemical and petroleum industries are shown. This book is intended for use by scientists in the areas of automatic control, mathematics, chemical engineering, and physics.